PENGUATAN BANTUAN HIDUP DASAR PADA WARGA RW 09 PONDOK RANGGON, CIPAYUNG, JAKARTA TIMUR: Strengthening Basic Life Support for Residents of RW 09, Pondok Ranggon, Cipayung, East Jakarta (Jurnal Pengabdian Masyarakat Kesehatan, 2020)
Basic life support is a basic action to help someone's life in a state of cardiac arrest and respiratory arrest. Death due to cardiac arrest and respiratory arrest can be overcome if the victim gets help. Basic life support can be done by anyone and anywhere immediately when the onset of cardiac arrest or stopping breathing. The purpose of this activity is to provide education and training to the community so that they can know and demonstrate the provision of basic life support in cases of cardiac arrest and respiratory arrest, choking, burns, poisoning and drowning. The implementation of education and training was given to the people in RT 09 RW 04, Pondok Ranggon, Cipayung, East Jakarta as many as 15 people, giving material and training with discussion lecture methods accompanied by demonstrations with power point media and CPR (Cardio Pulmonary Resuscitation) mannequins for 30 minutes, in addition to the community given education and training for victims of choking, poisoning, burns and drowning. The results of the evaluation in the pre-test showed a moderate level of knowledge of 46.7% and a low of 53.3%, whereas in the post-test obtained a high level of knowledge of 20% and a moderate of 80%. The basic life support education and training program that has been carried out is very useful for increasing public knowledge so it is also expected to be able to practice first aid in cases of cardiac arrest and respiratory arrest.